Triad of Micrognathia, Oligodontia, and Ankyloglossia in a Non-Syndromic Individual: A Case Report with Rare Presentation - Priti Shukla; Varsha Sharma; Shivesh Acharya; Shruti Singh (Journal of Pharmacy and Bioallied Sciences)
Deviations from the normal in the intrauterine formative phase have a permanent effect in an individual’s life. They can cause limitations in lifestyle from nil to severe. The sites may differ and hence would the presentations. Some of them together may form a syndrome while others could present as solitary findings. The below case report affirmed the presence of a unique non-syndromic triad of micrognathia, oligodontia and ankyloglossia which the authors named as “Budgie Triad.” Such rare findings can add to the existing knowledge and will help the clinicians in appropriate diagnosis and treatment planning helping in improving the patient’s quality of life.